The dark triad and corporate sustainability: An empirical analysis of personality traits of middle managers - Pelster, Matthias; Schaltegger, Stefan (Business Ethics, the Environment & Responsibility)

Attention triggers and investors' risk-taking - Arnold, Marc; Pelster, Matthias; Subrahmanyam, Marti G. (Journal of Financial Economics)
The paper investigates the impact of individual attention on investor risk-taking. We analyze a large sample of trading records from a brokerage service that allows its customers to trade contracts-for-differences (CFD), and sends standardized push messages on recent stock performance to its client investors. The advantage of this sample is that it allows us to isolate the "push" messages as individual attention triggers, which we can directly link to the same individuals' risk-taking. A particular advantage of CFD trading is that it allows investors to make use of leverage, which provides us a pure measure of investors' willingness to take risks that is independent of the decision to purchase a particular stock. Leverage is a major catalyst of speculative trading, as it increases the scope of extreme returns, and enables investors to take larger positions than what they can afford with their own capital. We show that investors execute attention-driven trades with higher leverage, compared to their other trades, as well as those of other investors who are not alerted by attention triggers.

Arbitrage in the Market for Cryptocurrencies - Crépellière, Tommy; Pelster, Matthias; Zeisberger, Stefan (Journal of Financial Markets)

Dark triad managerial personality and financial reporting manipulation - Mutschmann, Martin; Hasso, Tim; Pelster, Matthias (Journal of Business Ethics)

Two-period duopolies with forward markets - Cox, Caleb; Karam, Arzé; Pelster, Matthias (Review of Industrial Organization)
We experimentally consider a dynamic multi-period Cournot duopoly with a simultaneous option to manage financial risk and a real option to delay supply. The first option allows players to manage risk before uncertainty is realized, while the second allows managing risk after realization. In our setting, firms face a strategic dilemma: They must weigh the advantages of dealing with risk exposure against the disadvantages of higher competition. In theory, firms make strategic use of the hedging component, enhancing competition. Our experimental results support this theory, suggesting that hedging increases competition and negates duopoly profits even in a simultaneous setting.

Who participated in the GameStop frenzy? Evidence from brokerage accounts - Hasso, Tim; Müller, Daniel; Pelster, Matthias; Warkulat, Sonja (Finance Research Letters)
In January 2021, the GameStop stock was the epicenter of the first case of predatory trading initiated by retail investors. We use brokerage accounts to study who participated in this GameStop frenzy and how they performed. We investigate the extent to which investors’ personal and trading characteristics differ from the general population of retail investors. GameStop traders had a history of investing in speculative instruments, including stocks with lottery-like features. They were also more likely to close their positions before the peak of the bubble. At the onset of the frenzy, numerous retail investors also shorted GameStop. Overall, our results indicate that the GameStop frenzy was not a pure digital protest against Wall Street but speculative trading by a group of retail investors, in line with their prior high-risk trading behavior.
Keywords: Predatory Trading; Retail Investors; Trading Behavior

COVID-19 reporting and willingness to pay for leisure activities - Warkulat, Sonja; Krull, Sebastian; Ortmann, Regina; Klocke, Nina; Pelster, Matthias (Covid Economics)
The containment of COVID-19 critically hinges on individuals’ behavior. We investigate how individuals react to variations in COVID-19 reporting. Using a survey, we elicit individuals' perceived infection risk given various COVID-19 metrics (e.g., confirmed cases, reproduction rate, or case-fatality ratio). We proxy individuals' risk perception with their willingness to pay for the participation in everyday life and amusements events. We find that participants react to different COVID-19 metrics with varying sensitivity. We observe a saturation of sensitivity for several measures at critical limits used in the political discussion, making our results highly relevant for policy makers in their efforts to direct individuals to adhere to hygienic etiquette and social distancing guidelines.
Keywords: COVID-19 reporting; willingness to pay; willingness to accept

Dark Triad Personality Traits and Selective Hedging - Pelster, Matthias; Hofmann, Annette; Klocke, Nina; Warkulat, Sonja (Journal of Business Ethics)
We study the relationship between risk managers' dark triad personality traits (Machiavellianism, narcissism, and psychopathy) and their selective hedging activities. Using a primary survey of 412 professional risk managers, we find that managers with dark personality traits are more likely to engage in selective hedging than those without. This effect is particularly pronounced for older, male, and less experienced risk managers. The effect is also stronger in smaller firms, less centralized risk management departments, and family-owned firms.

Social interactions and asset pricing bubbles - Steiger, Sören; Pelster, Matthias (Journal of Economic Behavior & Organization)

COVID-19 and investor behavior - Ortmann, Regina; Pelster, Matthias; Wengerek, Sascha Tobias (Finance Research Letters)

Terror attacks and individual investor behavior: Evidence from the 2015–2017 European terror attacks - Hasso, Tim; Pelster, Matthias; Breitmayer, Bastian (Journal of Behavioral and Experimental Finance)

The disposition effect in a scopic regime: Data from a laboratory experiment - Liêu, Minh-Lý; Pelster, Matthias (Data in Brief)

The gambler’s and hot-hand fallacies: Empirical evidence from trading data - Pelster, Matthias (Economics Letters)

Framing and the disposition effect in a scopic regime - Liêu, Minh Ly; Pelster, Matthias (The Quarterly Review of Economics and Finance)

Pricing and issuance dependencies in SFP portfolios - Pelster, Matthias; Schertler, Andrea (Journal of Futures Markets)
We exploit a unique sample of structured financial products (SFPs) to analyze pricing and issuance dependencies among different types of such market‐linked investment vehicles. Our study provides evidence of cross‐pricing between products with complementary payoff profiles. Such dependencies may be explained by issuers’ efforts to generate order flow for products that supplement their current SFP risk exposure. Additionally, we observe issuance patterns in line with the argument that issuers exploit the complementarity payout profiles when bringing SFPs to market. Our study emphasizes cross‐pricing from a perspective not previously considered in the literature.
Keywords: cross‐pricing; discount certificate; hedging; issuance decisions; put warrants; structured financial products

Attracting attention from peers: Excitement in social trading - Pelster, Matthias; Breitmayer, Bastian (Journal of Economic Behavior & Organization)

Culture and the disposition effect - Breitmayer, Bastian; Hasso, Tim; Pelster, Matthias (Economics Letters)

Swarm intelligence? Stock opinions of the crowd and stock returns - Breitmayer, Bastian; Massari, Filippo; Pelster, Matthias (International Review of Economics & Finance)

Who trades cryptocurrencies, how do they trade it, and how do they perform? Evidence from brokerage accounts - Hasso, Tim; Pelster, Matthias; Breitmayer, Bastian (Journal of Behavioral and Experimental Finance)
We investigate the demographic characteristics, trading patterns, and performance of 465.926 brokerage accounts with respect to cryptocurrency trading. We find that cryptocurrency trading became increasingly popular across individuals of all different groups of age, gender, and trading patterns. Yet, men are more likely to engage in cryptocurrency trading, trade more frequently, and more speculative, respectively. As a result, men realize lower returns. Furthermore, we find that investors vary their trading patterns across different asset classes.
Keywords: Cryptocurrencies Bitcoin Trading Investor returns Demographics

Are cryptocurrency traders pioneers or just risk-seekers? evidence from brokerage accounts - Pelster, Matthias; Breitmayer, Bastian; Hasso, Tim (Economics Letters)
Are cryptocurrency traders driven by a desire to invest in a new asset class to diversify their portfolio or are they merely seeking to increase their levels of risk? To answer this question, we use individual-level brokerage data and study their behavior in stock trading around the time they engage in their first cryptocurrency trade. We find that when engaging in cryptocurrency trading investors simultaneously increase their risk-seeking behavior in stock trading as they increase their trading intensity and use of leverage. The increase in risk-seeking in stocks is particularly pronounced when volatility in cryptocurrency returns is low, suggesting that their overall behavior is driven by excitement-seeking.
Keywords: cryptocurrencies; bitcoin; investor; risk-seeking

About the Fear of Reputational Loss: Social Trading and the Disposition Effect - Pelster, Matthias; Hofmann, Annette (Journal of Banking & Finance)

Financial penalties and banks’ systemic risk - Köster, Hannes; Pelster, Matthias (The Journal of Risk Finance)

Bank stock performance and bank regulation around the globe - Pelster, Matthias; Irresberger, Felix; Weiß, Gregor N.F. (The European Journal of Finance)

Affect and stock returns - Breitmayer, Bastian; Pelster, Matthias (Journal of Behavioral and Experimental Finance)

Financial penalties and bank performance - Köster, Hannes; Pelster, Matthias (Journal of Banking & Finance)

The determinants of CDS spreads: evidence from the model space - Pelster, Matthias; Vilsmeier, Johannes (Review of Derivatives Research)

I’ll Have What S/he’s Having: A Case Study of a Social Trading Network - Pelster, Matthias (Proceedings of the International Conference on Information Systems)
Opinion leaders of an investment network can have a significant impact on capital mar-kets because their investment decisions are adopted by their peers and trigger large trad-ing cascades, increasing herding behavior and comovement among stock returns. This paper analyzes the interaction-based relations of traders from a large social trading plat-form and identifies the driving forces and the opinion leaders within a large online trading network as the nodes with the highest centrality and the highest force of infection, respec-tively. Relying on recent insights from epidemiological research, I maintain that central-ity identifies the most central traders in the network, while the expected force quantifies the most influential traders and their spreading power. I study the behavior and charac-teristics that set central and influential traders apart from other traders. The ability to identify focal points and their trading behavior within a trading network is important for investors, investment advisers, and policy makers.
Keywords: Online trading; investment advice; network modeling; Expected Force; herding.

Key Aspects of a Sustainable Health Insurance System in Germany - Pelster, Matthias; Hagemann, Vera; Laporte Uribe, Franziska (Applied Health Economics and Health Policy)